Claiming Abrogation of Pre-Islamic Religions; Contesting the Idea of Islam’s Abrogation to Previous Religions - Sa’dullah Affandy (UIN Sunan Kalijaga Yogyakarta, 2017)
This paper discusses surah Āli ‘Imrān [3]: 85 that is believed is not the abrogator of surah al-Baqarah [2]: 62. Surah al-Baqarah [2]: 62 is an inclusive ayah that informs the evidence of acknowledgement of the al-Qur’an upon the safety of adherents of religions. All ayahs of the al-Qur’an are the selected revelations that are operative in its nature. In the case of contradiction, they should be contextually understood based on their socio-historical background, as it is stated in its criteria that the abrogation is only enforced upon ayahs on law, and not for informative ayahs (ikhbāriyyah). This research employs a research method mapping the pros and the cons of interpretation using qualitative analysis. In collecting data, this research applies library research of the commentary books from classic to modern-contemporary periods as primary sources with socio-historical approaches. It also incorporates uṣūl fiqh and hermeneutics theories to analyse the text. This research finds out that Islam which is prescribed to the prophet Muhammad cannot abrogate the existence of pre-Islamic religions. The abrogation of religions is conflicted with the reality of the continuity of the Prophet Muhammad’s revelation. Islam is a religion of all prophets, and Islam that is prescribed to the prophet Muhammad is a continuation and a complementary to the legacies from previous religions. The idea of abrogating religions means to ignore part of the rules of an abrogation theory itself. Surah al-Baqarah [2]: 106 is not a base for the abrogation of previous religions. This ayah suggests a supposition, not a necessity of the abrogation.[Artikel ini mendiskusikan surat Āli ‘Imrān [3]: 85 yang diyakini sebagai ayat yang tidak me-nasakh surat al-Baqarah [2]: 62. Surah al-Baqarah [2]: 62 adalah ayat inklusif yang menginformasikan bukti pengakuan dari al-Qur’an atas keselamatan penganut agama-agama. Semua ayat al-Qur ’an adalah wahyu yang dipilih yang beroperasi sesuai sifatnya. Dalam kasus kontradiksi, mereka harus dipahami secara kontekstual berdasarkan latar belakang sosio-historisnya, seperti yang dinyatakan dalam kriterianya bahwa abrogasi (nasakh) hanya diberlakukan pada ayat-ayat hukum, dan bukan untuk ayat-ayat informatif (ikhbāriyyah). Penelitian ini menggunakan metode penelitian pemetaan pro dan kontra penafsiran dengan menggunakan analisis kualitatif. Dalam mengumpulkan data, ia menggunakan penelitian kepustakaan dari beberapa kitab tafsir dari masa klasik hingga periode modern kontemporer, sebagai sumber utama dengan pendekatan sosio-historis. Ini juga menggabungkan teori ushul fiqh dan hermeneutika untuk menganalisis teks. Penelitian ini menemukan bahwa Islam yang diwahyukan kepada Nabi Muhammad tidak dapat me-nasakh/membatalkan keberadaan agama pra-Islam. Pembatalan agama bertentangan dengan realitas kontinuitas wahyu Nabi Muhammad SAW. Islam adalah agama semua nabi, dan Islam yang diturunkan kepada Nabi Muhammad adalah kelanjutan dan pelengkap warisan dari agama-agama sebelumnya. Gagasan untuk membatalkan agama berarti mengabaikan sebagian dari aturan dari teori abrogasi/nasakh itu sendiri. Surah al-Baqarah [2]: 106 bukanlah dasar untuk pembatalan agama- agama sebelumnya. Ia menunjukkan sebuah dugaan, bukan keniscayaan pembatalan.]